Evaluation the Impact of Folic Acid Deficiency During Pregnancy and Preterm Birth - Alanazi, Aisha (British Journal of Healthcare and Medical Research, 2024)
Backgrounds: folate restriction and excessive supplementing leave epigenetic traces, suggesting the possibility of it generating unanticipated changes in the methyloma and hence in the phenotype of the mother and children in the short or long term. There is considerable evidence that insufficient or deficient folic acid status may be linked to pregnancy complications. Purposes: The purpose of this study to assess the impact of folic acid deficiency during pregnancy on incidence of preterm labor. Methods: The study utilised cross sectional study design with 245 pregnant women who selected conveniently from primary health centres in Hail region. The study assessed folic acid and its potential impact on preterm birth. Results: The result of the current study indicates that 245 pregnant women attended the study. The prevalence of folic acid deficiency is 44.8% (110/245). Looking at specific classification. The prevalence of folic acid deficiency is more prevalent among pregnant women in first trimester, it was noticed among 110 women from 190 which accounts 57.8%. The results of Chi square that look at the association between the folic acid use and preterm labour showed that there is statistical association between folic acid use during first trimester and gestational birth to be completed at aged 32 -36 week (χ2 = 4.56; p=0.024). In addition, females who did not consume folic acid causes pre term labor at gestational age 24 -27 weeks ((χ2 = 3.57; p=0.018). similarly, the result of odd ratio shows that pregnant women who did consume folic acid reduce risk of preterm labor 3-5 times compared with pregnant women who did not use folic acid. Conclusions: The study concluded that lower intake of folate levels and folic acid supplementation are significantly associated with a higher overall risk of overall PTB